The Association Between Triglyceride-Glucose Index as a Marker of Insulin Resistance and the Risk of Breast Cancer - Panigoro, Sonar Soni; Sutandyo, Noorwati; Witjaksono, Fiastuti; Siregar, Nurjati Chairani; Ramli, Ramadhan; Hariani, Ririn; Pangarsa, Eko Adhi; Prajoko, Yan Wisnu; Puruhita, Niken; Hamdani, William; Bayu, Dimas; Madjid, Mardiana; et al. (Frontiers in Endocrinology, 2021)
Background This study aims to evaluate the association and dose-response between triglyceride-glucose (TyG) index and breast cancer. Method This is a multicenter case-control study conducted in six public referral hospitals in Indonesia. Cases are individuals aged 19 years or above who were diagnosed with breast cancer within 1 year of diagnosis, based on histopathology and immunohistochemistry. Controls were recruited from corresponding hospitals. TyG index was determined by the formula: ln (fasting TG [mg/dl] × fasting glucose [mg/dl]). Results There were 212 participants in the breast cancer group and 212 participants in the control group. TyG index was higher in patients with breast cancer (median 8.65 [7.38, 10.9] vs. 8.30 [7.09, 10.84], p < 0.001). When compared with TyG quartile of Q1, Q4 was associated with an OR of 2.42 (1.77, 3.31), p < 0.001, Q3 was associated with an OR of 1.53 (1.21, 1.93), p < 0.001, Q2 was associated with an OR of 1.39 (1.12, 1.73), p = 0.002 for the risk of breast cancer. The dose-response relationship was nonlinear (p < 0.001). On univariate analysis, smoking (OR 2.15 [1.44, 3.22], p < 0.001), use of contraception (1.73 [1.15, 2.60], p = 0.008), alcohol consumption (OR 2.04 [0.96, 4.35], p = 0.064), and TyG Index >8.87 (OR 3.08 [1.93, 4.93], p < 0.001) were associated with risk of breast cancer. Independently associated with increased risk of breast cancer included smoking (OR 1.93 [1.23, 3.01], p = 0.004), use of contraception (OR 1.59 [1.02, 2.48], p = 0.039), and TyG Index >8.87 (OR 2.93 [1.72, 4.98], p < 0.001) Conclusion TyG index was associated with breast cancer in a nonlinear dose-response fashion.